Nearchus, Guides, and Place Names on Alexander's Expedition: Arrian's Indica 27.1 (FGrH 133 F 1 III). - James, Dylan (Mnemosyne, 2020)
The use of ὀνοµαζόµενα at Arr. Ind. 27.1 continues to puzzle scholars. This article uses the textual debate as a jumping-off point to explore Nearchus' presentation of naval guides and their role on Alexander's expedition, something which previous interpretations of the passage have not adequately considered. Through examination of all Nearchan fragments, I argue that providing local place names was a key aspect of a guide's role and significant for navigation. It is also suggested that the use of this verb may additionally refer to the Macedonians' practice of giving places new names or altering indigenous names; in this section, comparative material from New World conquest is brought to bear on the ancient evidence. In light of this analysis, I conclude that the manuscript reading of ὀνοµαζόµενα should be retained.